Analisis Kemampuan Mahasiswa Calon Guru Membuat Instrumen Penilaian Sikap - Nerita, Siska; Lufri, Lufri; Ellizar, Ellizar; Helendra, Helendra (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
Assessment plays an important role in determining the achievement of educational goals, so evaluation has a strategic role in the world of education. To ensure effective and efficient evaluation, it is necessary to use appropriate and reliable assessment instruments. Teachers have a big responsibility in developing the ability to create assessment instruments to measure students' attitudes, knowledge and skills, so that educational goals can be achieved accurately. The aim of this research is to analyze prospective teachers' abilities in designing attitude assessment instruments. This research uses a quantitative descriptive approach using student performance assessment instruments in creating attitude assessment instruments in biology learning. Indicators for measuring students' ability to create attitude instruments are 1) suitability of instrument components, 2) suitability of attitude assessment aspects with competency achievement indicators, 3) suitability of the rubric formulated with aspects of attitude assessment, 4) suitability of the formulation of the assessment rubric with statements, 5) Using language which is good and correct, does not use regional languages. The research results show that the ability of prospective biology teacher students in making attitude assessment instruments is still at medium criteria (67.82%).